Microstructural evolution of polyacrylonitrile fibers during industry-mimicking continuous stabilization - Jung-Eun Lee; Chae, Yang Ki; Lee, Dong Je; Jiho Choi; Chae, Han Gi; Kim, Tae Hwan; Lee, Sungho (Pergamon Press Ltd., 2022)
The industry-mimicking continuous stabilization of polyacrylonitrile (PAN) fibers was conducted in the temperature range of 180-270 C to investigate microstructural evolutions of the fibers with comprehensive analysis at various intermediate stages. The chemical reactions during stabilization induce elongational stress along the fiber axis. In the low-temperature regime (below 240 C), the cyclization reaction primarily occurs in the amorphous phase of the PAN structure, which possesses low thermal stability. The further stabilization including dehydrogenation and oxidation occurs actively even in the crystalline phase beyond 240 C. The small-angle X-ray scattering (SAXS) observation confirms that the stabilized PAN fibers have two kinds of microvoids: Major large microvoids with a diameter and a length of-6 and-17 nm, respectively, located between the microfibrils are formed during the spinning of precursors by the solvent-nonsolvent exchange, and small microvoids with a diameter and a length of-1 and-2 nm, respectively, which are presumably located at the ends of molecules, are generated by gas evolution from inside the fibers during stabilization. We believe that the integrated studies on stabilization with physical and chemical structural evolution of the microvoids provide significant information for industrial manufacturing of high-performance carbon fibers.(C) 2022 Elsevier Ltd. All rights reserved.